Exosome mediated delivery of Epigallocatechin 3 gallate as a novel approach to alleviate psoriasis symptoms through cytokine and apoptotic pathway modulation - Mohamed S. Kishta; Ahmed A. Abd-Rabou; Garo K. Sarkissian; Ahmed I. Elwakil; Dana M. Elsabry; Youssef M. Zagzoug; Sohaila R. Hussein; Ahmed N. Abdallah (Scientific Reports)
Abstract Psoriasis is a chronic skin disorder with significant individual and societal impacts. Current therapies often lack efficacy, are costly, or cause side effects, necessitating new treatments. This study explores regenerative therapies—exosomes, mesenchymal stem cells (MSCs), epigallocatechin-3-gallate nanoparticles (EGN), and EGN-loaded exosomes (EGN-Exo)—in regulating psoriasis-related markers (IL-6, IL-4, Bcl-2, Bax, NF-κB, CDC25B). An imiquimod-induced psoriasis model in Wistar rats was used, with six groups: negative control, positive control, and treatments (MSCs, exosomes, EGN, EGN-Exo). After seven days, ELISA revealed EGN-Exo most effectively reduced pro-inflammatory IL-6 and pro-apoptotic Bax while increasing anti-inflammatory IL-4 and anti-apoptotic Bcl-2. EGN-Exo also significantly lowered NF-κB and CDC25B, demonstrating superior anti-inflammatory effects. Apoptosis profiling showed EGN-Exo reduced late apoptotic cells, highlighting cytoprotective abilities. EGN had a moderate effect, while MSCs and exosomes showed modest improvements. Histopathological and immunohistochemical analyses confirmed EGN-Exo’s efficacy, notably reducing TGF-β expression. These findings suggest EGN-Exo combines EGCG’s antioxidant and anti-inflammatory properties with exosomes’ targeted delivery, offering a promising advanced therapy for psoriasis.